Vo2peak, Ve/VCO2, and Cardiac Remodeling Correlate with Long-Term Cardiovascular Outcome in Heart Failure Patients - Antonio Pagliaro; Luna Cavigli; Roberta Molle; Elisabetta Iardino; Francesca Anselmi; Francesca Righini; Luca Martini; Valerio Zacà; Giulia Elena Mandoli; Maria Concetta Pastore; Marta Focardi; Matteo Cameli; et al. (Journal of Cardiovascular Development and Disease)
Accurate prognostic stratification in patients with chronic heart failure and reduced ejection fraction (HFrEF) remains a significant clinical challenge. Many different parameters, including left ventricular (LV) and right ventricular (RV) function and cardiopulmonary exercise testing (CPET) parameters, are available in the literature. LV ejection fraction (LVEF) is the most used parameter in clinical practice. This study aimed to analyze CPET and echocardiographic data in patients under evaluation for heart transplantation (HTx) to identify the parameter that best correlates with cardiac events. Methods and Results. Echocardiography and CPET were performed in patients with HFrEF under evaluation for HTx. The population comprised 170 patients (mean age: 55 ± 9 years; 88% male; non-ischemic etiology: 63%). LVEF was 30.4 ± 7.6%, peak oxygen uptake (Vo2peak) was 17.08 ± 4.6 mL/Kg/min; minute ventilation (VE)/carbon dioxide production (Vco2) slope was 34.8 ± 8.7. During a follow-up of 4 ± 1 years, 37 hospitalizations, 4 deaths, 14 HTx, and 5 LV assist device implantation occurred. Patients who experienced major events had a lower Vo2peak (p < 0.005), higher VE/Vco2 slope (p < 0.005), greater LV end-systolic diameter (p < 0.005), and RV end-diastolic diameter (p < 0.005) than patients without events. Conversely, LVEF did not differ between these two groups. VE/Vco2 slope and RV dimensions significantly correlated with hard cardiac events (p = 0.019 and p = 0.008, respectively). Conclusions. In patients with HFrEF, parameters quantifying the system reserve (i.e., Vo2peak and VE/Vco2 slope) and those demonstrating advanced biventricular remodeling may help stratify the risk of cardiac events. Conversely, LVEF showed a limited prognostic value in this setting.